(untitled) (Biological Sciences - PJSIR, 2001)
Thiamine chloride hydrochloride (Fig 1), vitamin B 1 , is a very versatile ligand due to its variety of coordination sites (Talbert et al 1970). The pioneering studies on thiamine complexes Jed to the synthesis of only ionic complexes or salts of the type [HT] 2+ [MX4 ) 2• with no direct metal-nitrogen bonds (White and Drago 1971) due to the relative ease of protonation of the pyrimidine N( l ’) which was later overcome with the discovery of acetate buffer systems (Adeyemo and Shamin 1983a). Later work (Adeyemo et al 1986) on thiamine led to the synthesis of dinuclear and trinuclear complexes with metal-nitrogen and metal-metal bonds, and recently, a dimeric cadmium-thiamine complex has been prepared (Casas et al 1995). The present work was undertaken to investigate the ability of cobalt in form i ng polymetalli c complexes wi th vitami n B 1 , and interestin gly the present communication has posi tively revealed it.